Pengaruh Good Corporate Governance Terhadap Kinerja Keuangan Perusahaan Non-Cyclicals Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023 - Nadhifah Zhafarina Diaz; Enggar Diah Puspa Arum; Rita Friyani (LPPM Politeknik Piksi Ganesha, 2025)
This study aims to examine the effect of Good Corporate Governance mechanisms on corporate financial performance. The mechanisms include audit committee, independent commissioners, managerial ownership, and institutional ownership. Financial performance is measured using Return on Assets (ROA). The research object consists of consumer non-cyclicals food and beverage sub-sector companies listed on the Indonesia Stock Exchange during the period 2019–2023. This study employs a quantitative approach with a purposive sampling technique, resulting in 16 sample companies. Data analysis is conducted using multiple linear regression with SPSS version 26. The results indicate that the audit committee does not have a significant effect on financial performance, while independent commissioners, managerial ownership, and institutional ownership have a significant effect. Simultaneously, all Good Corporate Governance variables significantly affect corporate financial performance